A study on the finances of Kerala with Special reference to Public Revenue - V Johnson
This paper attempts to study the finances of Kerala with special emphasis on Public Revenue. The foregoing analysis shows that the finances of Kerala are in dire straits entailed by a more tolerant approach in revenue mobilization and ever increasing public expenditure and the resultant deficits and debt, leaving little for productive capital expenditure. The Government even finds it difficult to spare funds for the day- to-day operations and keep the Treasury afloat. One of the possible ways to address this fiscal debacle is to augment the revenue mobilization process along with scientific management of Public expenditure. This is however a challenging proposition. The present paper, however, sets focus on analysing the efficacy of the management of Revenue Receipts by the Government of Kerala, along with other factors impacting the finances of the State.